Ecological building design in Malaysian perspective - A guide for young architects / Mohd Jamil Idris - Idris, Mohd Jamil (2004)
Architects are made to design a good building. Not to mention, they are also responsible for the comfort living of the environment and the fulfill ness of people needs in spaces. In this millennium however, architects are challenged with enormous and thousands of issues to be taken care during design stage and process. Today buildings are produced for users without giving benefit to the ecology and human. A good design must have the equilibrium between this two. In order to create this, architect must be wiser and design a building more towards the environmental consideration. Unfortunately, most architects today have not been trained in any serious background on ecology and environmental biology. The understanding of the environment as a functioning natural system and the recognition of the dependence of built environment on ecology and environmental biology seem not to be acknowledged in architectural practice today. We are living in an era where natural resources are fast depleting; therefore, implementing passive environmental controls by sustainable development through modern thinking, or by advanced and sophisticated technology are essential. Inasmuch as symbolisms and meaning making are important to define 'humanness' of the built environment. All those involved with the built environment should learn to give more importance to ecology and environmental biology. This paper is an attempt to promote such thinking among the young architects or designers or even the building team. It is imperative that we should start to re-conceptualize the design of our built environment in a way to make better use of our current land and resources for assuring the quality of life for future generations.